Flexural Behavior of CFRP Laminate at Elevated Temperature - Abdalrahman, Rzgar M. (Kurdistan Journal of Applied Research, 2017)
A carbon fibre reinforced polymer (CFRP) laminate forms the surface part of an integrally heated tool. It was made up of carbon non-crimp triaxial fibre and SR8100 epoxy in accordance to the stacking sequence of [(0, ±45)/ (90, ±45)] S, using the resin infusion (RI) method. The laminate is heated up to 90ºC when the tool is operated; therefore under-standing the effect of temperature on the flexural properties is quite significant. This experimental study is carried out to investigate the flexural behaviour of the CFRP laminate and finding its flexural properties under the effect of elevated temperatures. For this purpose, various CFRP specim-ens were prepared and tested, using three point bending test method, at different temperature levels from room temperature to 90ºC. The results show that each of the flexural peak load, modulus and strength of the laminate decreases consistently with the increase of temperature. Also the laminate becomes slightly more flexible and significant loss occurs in its flexural modulus when the temperature elevates from 75ºC to 90ºC. The reduction in the flexural behaviour of CFRP is imputed to thermal softening of the epoxy polymer matrix whenever becomes closer to (HDT).